Antología del pensamiento crítico caribeño contemporáneo. - Valdés García, Felix (Antologías del pensamiento social latinoamericano y caribeño., 2017)
The texts gathered in this Anthology, beyond their belonging to Jamaica, Trinidad and Tobago, Martinique or Barbados, express the questioning of a greater totality: the reality of the Caribbean. They express the unity of the diverse, of the individual and the universal of an experience, of islands that are repeated over and over again, without even being equal to themselves, beyond physical proximity, fragility, factual continuity that history put at the mercy of imperial whims and the most unexpected social and cultural experiments of Western civilization. This selection aims to overcome the divisions and ignorance between peoples who share the same fate, similar inheritances and the same island sun; and thus be part of the critical work of Our America in the last half century.